2020
DOI: 10.7554/elife.54497
|View full text |Cite
|
Sign up to set email alerts
|

Systematic examination of low-intensity ultrasound parameters on human motor cortex excitability and behavior

Abstract: Low-intensity transcranial ultrasound (TUS) can non-invasively modulate human neural activity. We investigated how different fundamental sonication parameters influence the effects of TUS on the motor cortex (M1) of 16 healthy subjects by probing cortico-cortical excitability and behaviour. A low-intensity 500 kHz TUS transducer was coupled to a transcranial magnetic stimulation (TMS) coil. TMS was delivered 10 ms before the end of TUS to the left M1 hotspot of the first dorsal interosseous muscle. Varying aco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
95
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(137 citation statements)
references
References 80 publications
10
95
2
1
Order By: Relevance
“…Efficient induction of such assemblies can provide a powerful means to trigger or suppress a specific behavior (8,11), and can potentially guide us in understanding brain diseases (12) and to design more efficient brain machine interfaces (13). As with other perturbation techniques (14)(15)(16)(17), it is crucial to understand how parameters of stimulation, including the pattern of activation of specific neurons and the general state of the network dynamics, can be optimized for an efficient induction. This optimization can, however, be complicated, given the complex connectivity and dynamics of cortical networks.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient induction of such assemblies can provide a powerful means to trigger or suppress a specific behavior (8,11), and can potentially guide us in understanding brain diseases (12) and to design more efficient brain machine interfaces (13). As with other perturbation techniques (14)(15)(16)(17), it is crucial to understand how parameters of stimulation, including the pattern of activation of specific neurons and the general state of the network dynamics, can be optimized for an efficient induction. This optimization can, however, be complicated, given the complex connectivity and dynamics of cortical networks.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that GABAergic interneurons within the superior colliculus downregulate the activity of the nucleus itself [ 40 , 46 , 47 , 48 , 49 ]. Also, a recent study demonstrated that TUS increases GABAergic inhibition at the cortical level [ 9 ]. Accordingly, TUS may enhance the activity of superior colliculus GABAergic interneurons and, in turn, produce an overall reduction in superior colliculus output to the nucleus raphe magnus, thus leading to an increased R2 area ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, TUS of the primary motor cortex decreased corticospinal excitability and intracortical facilitation, increased GABAergic inhibition and reduced motor reaction task performance [ 8 , 9 ]. Conversely, motor evoked potential (MEP) amplitude was facilitated immediately after stimulation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…ON/OFF cycling is a frequently used parameter, particularly for the anterior nucleus of thalamus stimulation in epilepsy patients (Fisher et al, 2010). It is a potential approach to reduce energy delivery; however, acute stimulation studies showed a decreased treatment effect with cycling DBS compared to conventional DBS in ET (Swan et al, 2016), PD (Montgomery, 2005), and epilepsy (Molnar et al, 2006) patients.…”
Section: Cycling Dbsmentioning
confidence: 99%